An Initial Investigation of the Heating Properties of Conical Tents. - Cain,B (1984)
The following aspects of the heating of the Canadian Forces 10-Man Arctic Tent were examined: the effect of lining the tent; the time response of the internal tent temperature to a step increase in heat transfer to the tent; radiative heat transfer to the tent and convective heat loss from the tent. The internal tent temperatures were found to be significantly affected by the provision of a tent liner which increased the relative temperature per unit of heat input by 60% to 100%. Change in the radiative heat transfer to the tent also changed the internal tent temperature significantly. A hypothesis on the circulation pattern within the tent was proposed to explain the temperature distribution within the tent. The thermal response of these tents was found to be exponential with time constants of 1000 s and 1800 s for unlined and lined tents respectively. Internal tent temperatures of heated tents were found to remain approximately constant for wind velocities less than 5 m/s. Originator-supplied keywords include: Tents, Heating, Liner, Circulation, Time response, Radiative heat transfer, Wind, Temperature, and Insulation. Abstract in French.